Trabalho docente de mulheres em Goiânia-GO - Caetano, Daisy Luzia do Nascimento Silva (2014)
The teaching women's work falls within the framework of the patriarchal capitalist system, in which women's work is inserted into a strong level of precariousness. This research adopted the dialectical historical materialism as method and aimed to understand the spatial distribution of those women's work in Goiânia-GO from working conditions and daily life of workers. In face of it, becomes necessary to understand the plot of the female capitalism teaching work, thinking about the construction of teaching as a feminized precarious and fraught with professional activity that also influences and is influenced by goianiense metropolis. The work and unequal gender relations occur contributing to the formation of space in capitalism. The geographical analisys needs to start knowing that the work aims the space and therefore the teachers also work (re) producing urban space through their practices. People who produce the space are the responsible for its conception and transformation while living and realize it. In case of the workers they do that inside of a dialectical perspective: the service of capitalism and emancipatory direction. Were discussed the relationship between labor and capital as well as the sexual division of labor and the process of feminization of teaching in basic education, so then they could present teaching in Goiania. It was found by quantitative research that the process of feminization in Goiânia is similar to what occurs throughout Brazil. It was possible to understand that the work of teachers influences and is influenced by them in everyday life goianiense`s urban space life. Finally, qualitative research with teachers from state schools (State of Goiás) showed that personal and professional fulfillment is recurrent, as well as recognition of the precariousness of work.